Screening And Characterisation Of Potential Lipase Producing Strains From Arctic Samples - Ramle, Zakiah (2018)
Psychrotolerant microorganisms are widespread in natural cold environments ranging from deep sea to polar region and have a synergistic mechanism that allows them to adapt living in the cold. Possessing evolved cold active enzymes is one of the basic strategies of adaptation. Among the various cold enzymes is cold active microbial lipase, an enzyme that is able to hydrolyse triglycerols releasing fatty acids. Microbial lipases have gained notable attention for their widespread uses in industries. However, bulk production of enzymes direct from original microbe source is not feasible due to high maintenance cost thus will not be able to cater to high industrial demands.